A dual piezoelectric energy harvester with contact and non-contact driven by inertial wheel. (1st January 2021) - He, Lipeng; Zhao, Da; Li, Wei; Wu, Xiaoqiang; Cheng, Guangming
Highlights: A dual piezoelectric energy harvester with contact and non-contact is designed, manufactured and analyzed experimentally. Electrical signals of piezoelectric energy harvesters are collected when driven by inertia wheels of different masses. To conserve energy by recovering energy from idling of inertial wheels. Abstract: In this paper, a dual piezoelectric energy harvester with contact and non-contact driven by inertial wheel is designed to explore relationship between the mass of inertia wheel and the generator performance. This harvester consists of rectangular and circular lead zirconate titanate (PZT) plates, magnet and other support structure. The model is simplified and analyzed. The supporting structure of the energy harvester is manufactured by 3D printing technology, and the standard parts such as bolts are assembled. The test system is built and the prototype is tested under different rotation speed (from 100 to 1300 r/min) and inertia wheel mass (227, 287, 348 and 407 g). This study has shown that under constant driving conditions (1000 r/min), the optimal peak-to-peak voltage and root-mean-square power are 36.07 V, 5.31 V and 5.47mW, 0.05mW across the 5kΩ resistor. Moreover, the optimal root-mean-square voltage and power are 4.87 V, 613.01 mV and 1.15mW, 21.04 μW across the 10kΩ driven through an inertial wheel. Moreover, the energy conversion efficiency of the energy harvester is 18.27% driven at the inertial wheel of 407 g. Therefore, this energy harvester can be used to collect the energy stored during the idling of the inertia wheel to supply sensor.